Penerapan manajemen risiko terhadap perwujudan good corporate governance pada industri perbankan di indonesia - Yatimi, Muh Asrul (Maliki Interdisciplinary Journal, 2025)
The banking industry faces increasingly complex challenges due to global economic uncertainty, growing financial risks, and demands for transparent governance. This study aims to examine the relationship between risk management and the implementation of Good Corporate Governance (GCG) in Indonesian banking using a descriptive quantitative approach based on literature review. The findings indicate that effective risk management supports the implementation of GCG principles such as accountability, transparency, and responsibility. The integration of these systems enhances financial performance, reduces fraud, and strengthens banks’ internal oversight. However, challenges remain, including limited human resource capacity and weak compliance culture. Thus, institutional commitment and adaptive regulations are essential to ensure the synergy and sustainability of risk management and governance systems.